(untitled) (Alberta Journal of Educational Research, 2020)
The learning attainment of South African learners in mathematics is, as The International Mathematics and Science Study (TIMSS) data reveal, far from optimal. A key contributing factor is a shortage of competent and confident qualified mathematics teachers. The Post Graduate Certificate in Education (PGCE) offered at South African universities is a key qualification designed to address this challenge (amongst others, such as the Bachelor of Education [B.Ed.]). However, the success of the PGCE as a preparation for mathematics teachers is not without concern, as this paper argues. Using a qualitative case study focusing on a PGCE with a mathematics focus offered by a university of technology, this paper discusses the constraints identified by prospective teachers and teacher educators. Constraints are explored by focusing on the curriculum, partnerships, and policy relating to the delivery of the PGCE as true and critical to the efficacy of the program. The paper contributes to context-specific understanding of the constraints influencing the PGCE’s efficacy (as offered in 2014) in developing newly qualified teachers’ (NQTs) skills and knowledge to be confident and competent mathematics teachers. Keywords: Post Graduate Certificate in Education; mathematics; learning to teach; governance; curriculum. Les données d’une enquête internationale portant sur les acquis scolaires en mathématiques et en sciences (TIMSS) révèlent que le rendement des apprenants sud-africains en mathématiques est loin d’être optimal. Un facteur qui contribue de façon significative à ce phénomène est le manque d’enseignants qualifiés qui sont compétents et confiants. Le certificat d’études supérieures en éducation (PGCE) offert dans les universités en Afrique du Sud est une qualification importante conçue pour faire face à ce défi (le Baccalauréat en Éducation, entre autres). Toutefois, la réussite du PGCE comme outil de préparation pour les enseignants n’est pas sans inquiétude, comme le soutient cet article. En s’appuyant sur une étude de cas qualitative portant sur un PGCE avec une majeur en mathématiques et offert par une université de technologie, cet article discute des contraintes identifiées par de futurs enseignants et formateurs d’enseignants. Les contraintes sont examinées en se penchant sur le curriculum, les partenariats et les politiques relatives à la prestation du PGCE pour évaluer dans quelle mesure ils sont véritables et essentiels au programme. Cet article contribue à une compréhension, propre au contexte, des contraintes qui influencent l’efficacité du PGCE (tel qu’offert en 2014) à développer les compétences et les connaissances de nouveaux diplômés pour qu’ils soient des enseignants confiants et compétents. Mots clés diplôme d’études supérieures en éducation mathématiques; apprendre à enseigner; gouvernance; curriculum